Parameter Keselamatan Makanan Menurut Perspektif Hadith: Parameter of Food Safety from the Perspective of al-Hadith - Md Ariffin, Mohd Farhan; Ahmad, Khader; Man, Sa’adan (Online Journal of Research in Islamic Studies, 2018)
In food industry, safety aspects cannot be taken into account. Thus, concentration on hygiene, quality and safety aspects along the manufacturing process and product marketing activities are vital. According to Syed Qutb, critical observation on food is an emerging contemporary issue. However, population in most countries is not concerned about food safety. Therefore, discussion from Islamic perspective is an important attribute to appropriately understand the phenomenon of food as it relates to safety issues. Religious impact can helps encourage behavior change, application of positive value, increasing the level of food handling and reducing the risk of food safety. Religious texts are so powerful, easy to understand, helps increase the confidence as well as the sense of safety and security. The general idea is to have a coherent discussion from the perspective of hadith. Muslim consumers must begin to emphasize beyond halal aspects. In other words, consumers must not only ensure the food is halal, even clean, safe and in good quality (tayyib component).